ANALISIS POLA DASAR PADA PUISI LOUISE GLÜCK: A MYTH OF DEVOTION - Putri, Larasaty Luthfia; Chitra, Bima Prana (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2022)
This research is aimed to analyze the archetypal pattern and Greek mythology elements found in A Myth of Devotion (Glück, 2006). The analysis began with the kind of Greek mythology elements that exist in the poem. The following section analyzed the archetypes found in the poem, which examined based on the six phases that Frye has distinguished on Archetypal Criticism; Theory of Mythos that consists of four seasonal cycles of nature. This research used qualitative methodology. The sources were taken from various journals, books, and other library resources. The result of this research concluded as follows: 1) the Greek mythology elements appeared in A Myth of Devotion is the myth of Persephone’s abduction by Hades; and 2) The Mythos of summer; six phases of romance is successfully applied on the archetypes analysis that occurred on the myth of Persephone and Hades in both poems.